The Role of STEM-Based Sustainability in Business and Management Curricula: Exploring Cognitive and Affective Outcomes in University Students. (August 2022) - Craig, Christopher A.; Petrun Sayers, Elizabeth L.; Gilbertz, Susan; Karam, Rita; Feng, Song
To address deficiencies in STEM and sustainability in business management and intra-university curricula, we developed and implemented an interdisciplinary STEM-based sustainability curriculum at a university in the Western United States. Six classes participated in curricular efforts including in-person and online sections of a business management course, in-person and online sections of a general elective STEM course, and a matched control course for each ( n  = 214). We systematically designed, developed, and implemented curricular interventions—multi-week STEM-based business sustainability modules—using the case teaching method. A comprehensive evaluation with pre- and post-tests was conducted to assess student sustainability cognition and affect. Significant results emerged for sustainability cognition including the environmental, social, and economic dimensions of sustainability. Counterintuitively, student sustainability affect did not improve. However, sustainability cognition and affect were significantly correlated on the post-test for treatment students, an indication that cognitive and affective changes share the same directionality. Discussion, implications, limitations, and future research directions are provided.